2016
DOI: 10.7120/09627286.25.1.029
|View full text |Cite
|
Sign up to set email alerts
|

Farmer attitudes to injurious pecking in laying hens and to potential control strategies

Abstract: 21Farmers' recognition of health and welfare problems, and their responses to related intervention programmes 22 such as those to reduce injurious pecking (IP) in hens, directly influence the welfare of animals in their care. 23Changing those responses can be achieved through a re-positioning of social drivers as well as from individual 24 behaviour. This study begins by considering how certain levels of plumage damage become normalised while 25 others might be considered unacceptable. Drawing upon in-depth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…With respect to the literature, an inter-observer WK of 0.88 was reached for the back area between researchers, similar to values reported by Kjaer et al [13], who found a WK of 0.82 between researcher teams using a visual assessment of plumage damage. Between farmers, lower values were reported (kappa of 0.50) when ranking photographs of FD damage only [27]. Some variation between assessors’ perceptions as to what is considered an acceptable level of FD is also unavoidable [12,27]; therefore, written descriptions and visual depictions of each score were included in the final system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the literature, an inter-observer WK of 0.88 was reached for the back area between researchers, similar to values reported by Kjaer et al [13], who found a WK of 0.82 between researcher teams using a visual assessment of plumage damage. Between farmers, lower values were reported (kappa of 0.50) when ranking photographs of FD damage only [27]. Some variation between assessors’ perceptions as to what is considered an acceptable level of FD is also unavoidable [12,27]; therefore, written descriptions and visual depictions of each score were included in the final system.…”
Section: Discussionmentioning
confidence: 99%
“…Between farmers, lower values were reported (kappa of 0.50) when ranking photographs of FD damage only [27]. Some variation between assessors’ perceptions as to what is considered an acceptable level of FD is also unavoidable [12,27]; therefore, written descriptions and visual depictions of each score were included in the final system. In a trial of the modified system with the accompanying scoring guide, the three Arkell staff members who scored 50 birds within the same room containing approximately 700 birds (and, thus, likely scored different birds) found a fairly similar FD prevalence suggesting that it gave a reasonable representation of all birds within the room.…”
Section: Discussionmentioning
confidence: 99%
“…Other important factors that influenced FAW improvement is the space and workload required to address animals' needs [84,93,94]. Several authors have reported that farmers were reluctant to applying evidence-based FAW recommendations when it had implications for labour, space and time investment, regardless of the production system [9,16,72,76,77,81,86,[94][95][96][97][98]. In contrast FAW interventions that could be carried out quickly, in a time-efficient manner, were reported to be easily adopted by farmers [86].…”
Section: Time and Spacementioning
confidence: 99%
“…It is happening with the expanding incorporation of welfare criteria in environmental certification and assurance schemes, but these are often limited to relatively high-end food supply chains [ 55 , 56 ]. It is also happening in some of the more innovative responses to legislative change, for example in schemes to enable the enrichment of laying hens following the banning of beak-trimming in the EU [ 57 ] and in the emergence of free farrowing systems for pigs following the EU ban on farrowing crates [ 58 ].…”
Section: New Challengesmentioning
confidence: 99%